2014
DOI: 10.1109/tit.2014.2304451
|View full text |Cite
|
Sign up to set email alerts
|

A New Method to Compute the 2-Adic Complexity of Binary Sequences

Abstract: Abstract. In this paper, a new method is presented to compute the 2-adic complexity of pseudo-random sequences. With this method, the 2-adic complexities of all the known sequences with ideal 2-level autocorrelation are uniformly determined. Results show that their 2-adic complexities equal their periods. In other words, their 2-adic complexities attain the maximum.Moreover, 2-adic complexities of two classes of optimal autocorrelation sequences with period N ≡ 1 mod 4, namely Legendre sequences and Ding-Helle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 15 publications
2
49
0
Order By: Relevance
“…In this section, using the periods which have been determined in Section 3, we will give a lower bound on the 2-adic complexity of modified Jacobi sequence. In order to derive the lower bound, the following two results will be useful, which can be found in [18] and [3] respectively. Lemma 4 [18] Viewing A as a matrix over the rational fields Q, if det(A) = 0, then gcd S(2), 2 N − 1 |gcd det(A), 2 N − 1 .…”
Section: A Lower Bound On the 2-adic Complexity Of Jacobi Sequencementioning
confidence: 99%
See 3 more Smart Citations
“…In this section, using the periods which have been determined in Section 3, we will give a lower bound on the 2-adic complexity of modified Jacobi sequence. In order to derive the lower bound, the following two results will be useful, which can be found in [18] and [3] respectively. Lemma 4 [18] Viewing A as a matrix over the rational fields Q, if det(A) = 0, then gcd S(2), 2 N − 1 |gcd det(A), 2 N − 1 .…”
Section: A Lower Bound On the 2-adic Complexity Of Jacobi Sequencementioning
confidence: 99%
“…In 2010, Tian and Qi showed that the 2-adic complexity of all the binary m-sequences is maximal [16]. Afterwards, Xiong et al [18] presented a new method using circulant matrices to compute the 2-adic complexities of binary sequences. They showed that all the known sequences with ideal 2-level autocorrelation have maximum 2-adic complexity.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, in [2], Ding et al proved that the 2-adic complexities of Legendre sequences and Ding-Helleseth-Lam sequences with optimal autocorrelation are also maximal. Then, using the same method as that in [22], Xiong et al [23] pointed out that two other classes of sequences based on interleaved structure have also maximal 2-adic complexity. One of these two classes of sequences was constructed by Tang and Ding [15], which has optimal autocorrelation, the other was constructed by Zhou et al [24], which is optimal with respect to the Tang-Fan-Matsufuji bound [16].…”
Section: Introductionmentioning
confidence: 99%